Fungsi dan Makna Seni Jemblung Murtadho dari Jawa Timur - Harpang Yudha Karyawanto (Universitas PGRI Adi Buana Surabaya, 2017)
This research examines the problem of the value of Jemblung Murtadho art.The research object is Jemblung’sart Sadat Kawedar Murthado in Tunjung village, Udanawu subdistrict, Blitar regency. The purpose of this researchare: (1) examine the meaning of art performing of Jemblung Murthado, (2) examine the art function of Jemblung inperformances. The research approach is using qualitative approach with ethnomusicology method. Data collectiontechniques is using: (1) recording techniques, audio and audiovisual, (2) note taking, (3) interviewing, (4) literaturestudy and documentation analysis. The steps in analyzing the data was done by: Data transcription, understandingdata, classification, and data condification. While for the validity of data, the researcher (1) doing triangulation, (2)doing peer debriefing, and (3) doing member check and audit trial.The research on music in Jemblung’s Murtadhowith ethnomusicology approach will be reviewed by the textual and contextual. The textual elements will expose theproblems concerning aspects of his music while contextual elements will explain about the culture of the community as asupporter of the arts.The results of this research on forms of art music Jemblung covered all of musikologic aspects,namely: (a) the concept of music in Jemblung’s, it has Java’s concept of Islamic art music, which is a form of praisesongs with the addition of story as a media in religious proselyzing, (b) the form of presentation is divided into twoelements among the elements of music and literature, and (c) The means of presentation which includes place, time,players, and costumes. The findings regarding the social function of Jemblung’s Murtadho include: (a) as aestheticsatisfaction,(b) as an entertainment,(c) as a means of communication, (d) as a strengthen compliance with social norms,(e) as a validation of social institutions, and religious rituals, (f) as a contribution to the sustainability and stability ofculture, (g) as an educational tool for the community, (h) as a community mental forming,(i) as a means of obtainingincome and (j) as a Host side traders to sell.